Hydroxy esters atmospheric degradation: OH and Cl reactivity, products distribution and fate of the alkoxy radicals formed - Straccia Cepeda, Vianni Giovanna (2023)
Kinetic studies of the reaction of ethyl glycolate HOCH2C(O)OCH2CH3 with OH radicals (kOH) and Cl atoms (kCl) have been conducted by the relative method using a glass atmospheric reactor by “in situ” Fourier Transform Infrared (FTIR) and Gas Chromatography equipped with flame ionization detection by Solid Phase Micro Extraction (GC-FID/SPME) at room temperature and atmospheric pressure. The following relative rate coefficients were determined using several reference compounds and two different techniques: kEG + OH-FTIR = (4.36 ± 1.21) × 10−12; kEG + OH-GC-FID= (3.90 ± 0.74) × 10−12; and kEG + Cl-GC-FID= (6.40 ± 0.72) × 10−11 all values in units of cm3.molecule−1.s−1. Complementary product studies were performed under comparable conditions to the kinetic tests, in order to identify the reaction products and to postulate their tropospheric oxidation mechanisms. The reaction of OH radicals and Cl atoms with ethyl glycolate initiates via H-atom abstraction from alkyl groups of the molecule. Formic acid was positively identified as a reaction product by FTIR. On the other hand, formaldehyde, acetaldehyde, glycolic acid; and formic acid were identified by the GC-MS technique. The Structure–Activity Relationship, (SAR) calculations were also implemented to estimate the more favorable reaction pathways and compare them with the products identified. Tropospheric lifetimes of τOH = 34 h and τCl = 5.5 days were estimated to determine how these investigated reactions might affect the air quality. In this sense, average ozone production of [O3] = 0.75 and a Photochemical Ozone Creation Potential, POCP, of 38 were calculated for the hydroxyl ester studied.